An evaluation of Zimbabwe`s prevention of mother-to-child transmission (PMTCT) programme to reduce the infant mortality rate: a case study of Chitungwiza - Chihota, Kudakwashe Elliot (Midlands State University, 2017)
The focus of this research was on exploring the role of the PMTCT Programme in the reduction of the infant mortality rate with particular reference to Chitungwiza in Zimbabwe. HIV/AIDS is a global concern that calls for utmost attention from development practitioners. Mother-to-child transmission (MTCT) of HIV is the most common route of infection in paediatric HIV acquisition. It contributes more than 90% of paediatric HIV infections. Widespread ignorance of the PMTCT Programme has contributed to the spread of HIV affecting the health service delivery in Chitungwiza and other parts of the country. The descriptive research design was used in order to depict the situation in the selected area of study (Chitungwiza) in terms of the infant infection of HIV. An explanatory research design was also applied during the research in order to explain the PMTCT programme, as regards its contribution in promoting maternal health. The study population comprised participants who were pregnant women attending the Ante-Natal Clinic (ANC). Hospital staff as well as hospital reports and records were also important sources of information. The researcher employed interviews as a data collection instrument. On the basis of the interview responses, the researcher established that, indeed, low male participation, their attitude as well as lack of knowledge have been the main factors hampering the effectiveness of the PMTCT Programme. In light of this, the researcher took special note of the views from key respondents and proposed recommendations for a more successful PMTCT Programme to fully deliver the intended results.